1999
DOI: 10.1038/sj.onc.1202828
|View full text |Cite
|
Sign up to set email alerts
|

Bcr: a negative regulator of the Bcr-Abl oncoprotein

Abstract: Chronic myelogenous leukemia is typically characterized by the presence of the Philadelphia chromosome (Ph) in which 5' portions of the BCR gene are fused to a large portion of the ABL gene. Our studies and those of others indicate that Bcr sequences within the Bcr-Abl oncoprotein are critically involved in activating the Abl tyrosine kinase and actively participate in the oncogenic response, which is generated by the Bcr-Abl oncoprotein. We investigated the role of the Bcr protein in the oncogenic eects of Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 24 publications
2
49
0
Order By: Relevance
“…We have previously showed that overexpression of Bcr relative to Bcr-Abl is required for Bcr's inhibitory effects (Wu et al, 1999;Lin et al, 2001). In addition, it has been reported that BCR-ABL/BCR transcript ratios can be used as an important diagnostic parameter for aggressive behavior of CML patients, suggesting a possible role of normal Bcr in CML pathogenesis (Moravcova´et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously showed that overexpression of Bcr relative to Bcr-Abl is required for Bcr's inhibitory effects (Wu et al, 1999;Lin et al, 2001). In addition, it has been reported that BCR-ABL/BCR transcript ratios can be used as an important diagnostic parameter for aggressive behavior of CML patients, suggesting a possible role of normal Bcr in CML pathogenesis (Moravcova´et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The first exon also contains two serine-rich domains that bind specifically to the SH2 domain of Abl in a non-phosphotyrosine-dependent manner (Pendergast et al, 1991). These serine-rich sequences in the phosphoserine form are involved in downregulating Bcr-Abl oncogenic activity (Wu et al, 1999;Lin et al, 2001;Hawk et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of these findings, several induceable vector systems were tested to introduce a transcriptionally silent form of the BCR cDNA into Bcr-Abl cells, which would permit induction of BCR gene expression to determine the initial effects of Bcr on the Bcr-Abl oncogenic phenotype. The tetracycline (Tet) repression system was chosen (Wu et al, 1999). In order to maximize the induction of the Bcr protein and to insure a low level of synthesis of exogenous Bcr in the non-induced condition, various clones of transfected Bcr-Abl expressing cells were selected in soft agar (as a means to select oncogenic Rat-1 cell clones) under neo selection conditions.…”
Section: Bcr(64-413) Expression In CML Cell Lines and Primary Culturementioning
confidence: 99%